2021
DOI: 10.1121/10.0003606
|View full text |Cite
|
Sign up to set email alerts
|

The near field, Westervelt far field, and inverse-law far field of the audio sound generated by parametric array loudspeakers

Abstract: The near and far fields of traditional loudspeakers are differentiated by whether the sound pressure amplitude is inversely proportional to the propagating distance. However, the audio sound field generated by a parametric array loudspeaker (PAL) is more complicated, and in this article it is proposed to be divided into 3 regions: near field, Westervelt far field, and inverselaw far field. In the near field, the audio sound experiences strong local effects and an efficient quasilinear solution is presented. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…14,15 It has also been demonstrated that the predictions obtained using the Westervelt equation are accurate enough except for observation points close to the radiation surface of the PAL. 14,15 After using the successive method, 16 the quasilinear solution of the audio sound based on the Westervelt equation can be seen as the radiation from a virtual volume source with the source density proportional to the product of the ultrasound pressure. 17,18 The expression of the solution is therefore a threefold integral over the three dimensional space.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…14,15 It has also been demonstrated that the predictions obtained using the Westervelt equation are accurate enough except for observation points close to the radiation surface of the PAL. 14,15 After using the successive method, 16 the quasilinear solution of the audio sound based on the Westervelt equation can be seen as the radiation from a virtual volume source with the source density proportional to the product of the ultrasound pressure. 17,18 The expression of the solution is therefore a threefold integral over the three dimensional space.…”
Section: Introductionmentioning
confidence: 92%
“…8,11 However, the ultrasound beams are assumed to be exponentially attenuated in each direction, which is not true in reality because of the complexity of the ultrasound beams in the near field, where the majority of the nonlinear interactions take place. Furthermore, the far field is found to be more than 10 meters away from a PAL when its size is larger than 0.04 m, 15,28 which is too far when compared to real applications. Therefore, differences between predictions and measurements continue to be observed, even for the sound pressure 4 meters away from the PAL.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations